Do cinema à comissão da verdade: uma história das memórias de ex-presas políticas na ditadura civil-militar brasileira (1989-2014) - Carvalho, Maria Aline Silva (2024)
This study sought to construct a history of memories about the experience of women's imprisonment, based on the understanding that in the scope of historiography and memoirs, there was a privilege regarding these narratives to address the civil-military dictatorship in Brazilian territory in 1964-85. We aim to analyze the transformation of the production and uses of the memories of these former political prisoners, in an analysis of the first years of democratic recovery, passing through the creation of transitional justice policies, until the work was carried out and the report of the National Truth Commission was released in 2014. We selected as sources of analysis the documentary Que bom te ver viva (1989) by Lúcia Murat and the book report Mulheres que foram à luta armada (1998) by Luiz Maklouf for having used more specifically the narrative of women who were arrested. This selection took place based on the testimonies of former political prisoners produced by the CNV, which are also part of the sources analyzed, which operated between 2012 and 2014. To understand how these women created these narratives in different periods, between the 1980s and 90s and, later, through a State initiative such as the Truth Commission. The CNV aimed to investigate Human Rights violations committed 1946-1988, by the Brazilian State. It was an instrument used to build a documentary collection that contributed to bringing the “historical truth” about the facts and prevented an authoritarian regime from being implemented in Brazil again. The use of testimony as a way of producing the narratives of militants, family members and military personnel was part of the methodology adopted, with a specific definition of subjects considered by the Commission as 'civilian victims'. In this way, we intend to analyze how this memory was produced and transformed by these political prisoners in different political situations.